2009
DOI: 10.1161/strokeaha.108.535070
|View full text |Cite|
|
Sign up to set email alerts
|

Postpublication External Review of the Japanese Guidelines for the Management of Stroke 2004

Abstract: Background and Purpose-Many guidelines for management of stroke have been published throughout the world, but no postpublication external review of any set of stroke guidelines by users, using standard checklists, has been reported. The purpose of this article is to present the results of an external review of the Japanese Guidelines for the Management of Stroke 2004, conducted several months postpublication. Methods-Forty-one evaluators, who had not been involved in developing the guidelines, were selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Therefore, a postpublication evaluation of the guidelines was performed by people representing these groups as part of the 2003 MHLW Science Research. 1 In that evaluation, a total of 41 people participated, including 22 stroke specialists, 8 nonspecialists, and 11 health care professionals who had not directly participated in the development of GL2004. For the evaluation, 3 international assessment criteria (AGREE, the procedure of Shaneyfelt et al and COGS) were used, as described in our article published in Stroke.…”
Section: Preface For 2009 Versionmentioning
confidence: 99%
“…Therefore, a postpublication evaluation of the guidelines was performed by people representing these groups as part of the 2003 MHLW Science Research. 1 In that evaluation, a total of 41 people participated, including 22 stroke specialists, 8 nonspecialists, and 11 health care professionals who had not directly participated in the development of GL2004. For the evaluation, 3 international assessment criteria (AGREE, the procedure of Shaneyfelt et al and COGS) were used, as described in our article published in Stroke.…”
Section: Preface For 2009 Versionmentioning
confidence: 99%
“…Therefore, there is a pressing need to improve patients’ abilities to self-manage their social life and activities. Previous reports have shown that establishing goals during the early phase of hospitalization hastens effective rehabilitation [1–3]. …”
Section: Introductionmentioning
confidence: 99%
“…Ischemic neuronal damage is known to be related to mitochondria and endoplasmic reticulum dysfunction, activated oxygen species, and increased expression of inflammatory cytokines and proteolytic enzymes (Heo et al, 1999;Zhao et al, 2004;Sarabi et al, 2008), but the detailed molecular mechanisms are still unknown. In spite of the development of various therapeutic strategies, including thrombolysis with tissue-type plasminogen activator or free radical scavengers (Yepes et al, 2000), it has been difficult to completely cure because of the intractable severe subsequent complications such as paralysis and cognitive dysfunction (Shinohara et al, 2009;Yagi et al, 2009). Thus, clarification of the detailed mechanisms responsible for the development of ischemic neuronal damage is urgently required.…”
Section: Introductionmentioning
confidence: 99%